Intratypic Electrophoretic Variation of Structural and Non-structural Polypeptides of Human Influenza A Viruses - Oxford, J. S.; Corcoran, T.; Schild, G. C. (Journal of General Virology, 1981)
SUMMARY Intratypic electrophoretic mobility differences in high resolution SDS-polyacrylamide gels were detected between corresponding matrix (M) proteins, nucleoproteins (NP), haemagglutinin (HA) and the non-structural polypeptides NS1 and NS2 induced in Vero cells by human influenza A viruses of the antigenic subtypes H1N1 and H3N2. Such phenotypic differences were distinguishable in both H1N1 and H3N2 viruses isolated in single school and city outbreaks. Additional intratypic variation was detected in the biological property of virus plaquing in MDCK cells. Although the biochemical basis is not established, phenotypic variation could represent an additional factor influencing the epidemiology of influenza A viruses.
Keywords: intratypic variation